The Influence of Workplace Communication and Work Motivation on Employee Performance at Besemah Hospital, Pagar Alam City - Meri Kartika Sari; Sastra Mico; Zulaiha Zulaiha (The Future of Education Journal, 2026)
This study aims to empirically analyze the influence of workplace communication and work motivation on employee performance at Besemah Hospital in Pagar Alam, both partially and simultaneously. This is a quantitative study using an associative approach. The population in this study comprises all employees of Besemah Hospital in Pagar Alam City, totaling 574 people. Using the Slovin formula at a precision level of 7%, a sample of 151 respondents was selected using probability sampling. Data collection was conducted by distributing a structured questionnaire that had been tested for validity and reliability. The data analysis methods used included classical assumption tests (normality test), multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing (t-test and F-test) using SPSS version 26 software. The partial results of the study indicate that workplace communication has a positive and significant effect on employee performance, with a calculated t-value (2.332) > the critical t-value and a significance level of 0.021 < 0.05. Work motivation was also found to have a positive and significant partial effect, with a calculated t-value (14.271) > the critical t-value and a significance level of 0.000 < 0.05. Simultaneously, the F-test results show that workplace communication and work motivation have a significant effect on employee performance, with a calculated F-value of 544.953 and a significance level of 0.000 < 0.05. The coefficient of determination (Adjusted R-Square) was 0.880, indicating that workplace communication and work motivation account for 88% of the variation in employee performance, while the remaining 12% is explained by other variables outside the scope of this study. Based on these results, it is recommended that the management of Besemah Hospital continue to optimize a transparent internal communication system and enhance employee motivation programs to maintain excellent quality of healthcare services.